The epigenetic regulatory effect of histone acetylation and deacetylation on skeletal muscle metabolism-a review - Xu, Junjie; Li, Chenglong; Kang, Xiaolong (Frontiers in Physiology, 2023)
Skeletal muscles, the largest organ responsible for energy metabolism in most mammals, play a vital role in maintaining the body’s homeostasis. Epigenetic modification, specifically histone acetylation, serves as a crucial regulatory mechanism influencing the physiological processes and metabolic patterns within skeletal muscle metabolism. The intricate process of histone acetylation modification involves coordinated control of histone acetyltransferase and deacetylase levels, dynamically modulating histone acetylation levels, and precisely regulating the expression of genes associated with skeletal muscle metabolism. Consequently, this comprehensive review aims to elucidate the epigenetic regulatory impact of histone acetylation modification on skeletal muscle metabolism, providing invaluable insights into the intricate molecular mechanisms governing epigenetic modifications in skeletal muscle metabolism.